Mulheres na TPM: o corpo e a configuração de modos de ser mulher na capa da revista feminina - Vanessa Costa Trindade (2019)
Based on the question “How does the women’s magazine Tpm, from the bodies that it brings verbally and visually printed on its covers, continuously institutes ways of being a woman in Brazil today?”, we mobilized the notions of media dispositif (ANTUNES; VAZ, 2006) and of dispositive of sexuality (FOUCAULT, 1984) to observe how the covers of the women’s magazine Tpm act in establishing ways to be a woman through her visual text (APRIL, 2007; 2013) and to reflect on the social regulation of the bodies that goes through the media. The analysis of the covers takes place according to the dimensions of the visual text proposed by Abril: the visuality (set of signifiers that conform the plane of the expression of a visual text and that constructs its coherence), the viewing (look that comes from places of enunciation constructed and assimilated according to the social positions of the subjects) and the image (part and result of the social imaginaries, which acts in the creation of a certain sense of reality, of the common). In seizing such text, we take the cover as a poster in urban space (VAZ, TRINDADE, 2013), which can reach virtual environments in countless reproductions and comments (JENKINS, FORD; GREEN, 2014). We also believe in the notion of portrait (FABRIS, 2004), since the cover of Tpm can be seen as a poster that usually contains a portrait, a way of personal affirmation that is nevertheless shaped by the social process in which the individual is inserted. Our conclusions point to the idea that the cover, due to its shape and its mode of circulation, precedes and produces the magazine; that Tpm is concerned with responding to some social anxieties related to women and seems to be ahead of some magazines, but does not bring anything new to the discussions that it proposes; the thematic work of the magazine reiterates a traditional version of visibility as something positive, however, it always implies erasures and the invisible. We also perceive the constitution of the methodological path in the research process – it does not precede the work; and the emergence of the possibility of articulation between the media dispositif and the dispositif of sexuality – at one point, the dispositif of sexuality forms the journal, in another, the media dispositif.